If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -3)(2X + -10) = 0 Reorder the terms: (-3 + X)(2X + -10) = 0 Reorder the terms: (-3 + X)(-10 + 2X) = 0 Multiply (-3 + X) * (-10 + 2X) (-3(-10 + 2X) + X(-10 + 2X)) = 0 ((-10 * -3 + 2X * -3) + X(-10 + 2X)) = 0 ((30 + -6X) + X(-10 + 2X)) = 0 (30 + -6X + (-10 * X + 2X * X)) = 0 (30 + -6X + (-10X + 2X2)) = 0 Combine like terms: -6X + -10X = -16X (30 + -16X + 2X2) = 0 Solving 30 + -16X + 2X2 = 0 Solving for variable 'X'. Factor out the Greatest Common Factor (GCF), '2'. 2(15 + -8X + X2) = 0 Factor a trinomial. 2((3 + -1X)(5 + -1X)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(3 + -1X)' equal to zero and attempt to solve: Simplifying 3 + -1X = 0 Solving 3 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1X = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1X = 0 + -3 -1X = 0 + -3 Combine like terms: 0 + -3 = -3 -1X = -3 Divide each side by '-1'. X = 3 Simplifying X = 3Subproblem 2
Set the factor '(5 + -1X)' equal to zero and attempt to solve: Simplifying 5 + -1X = 0 Solving 5 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1X = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1X = 0 + -5 -1X = 0 + -5 Combine like terms: 0 + -5 = -5 -1X = -5 Divide each side by '-1'. X = 5 Simplifying X = 5Solution
X = {3, 5}
| 26x+1=5(5x+4) | | n+(n+2)+(n+4)=66 | | -8-x=10 | | -10=x+8 | | 5(x+4)+4(x-1)=106 | | 5(6-5x)=67 | | 5x-20+2x+8= | | 26x-1=5(5x-4) | | 9(x-2)=3(3x-5)-3 | | (3x+2)*(-x-12)=0 | | 5x-20+2x+8+6x+4= | | -5(8x-2y-8)= | | 15x-14= | | 458*x^2-34*x=0 | | 5-3x(4-6)= | | =27w^3*z^6-8*s^3 | | (X+2)*(x-6)=0 | | -5(4-x)=-10 | | 2(-3x-6)=-66 | | x-1(x-2)=7(x+2) | | 10y=164 | | -6x-8=4x-58 | | x+3=6x+3 | | 5-(-24)= | | 3x+7=19+5x | | -3x-1=6x-93 | | -2x+10=4-x | | -6+5x=-x-6 | | -6x+9=23+x | | 2*(x+7)=3*(2x-5) | | 6-5x=4x+6 | | 6x-9=9-9x |